2020
DOI: 10.1101/2020.07.07.192278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Different Microplastics on Nematodes in the Soil Environment: Tracking the Extractable Additives using an Ecotoxicological Approach

Abstract: ABSTRACTWith an increasing interest in the effects of microplastic in the soil environment, there is a need to thoroughly evaluate potential adverse effects of these particles as a function of their characteristics (size, shape, and composition). In addition, extractable chemical additives from microplastic have been identified as an important toxicity pathway in the aquatic environment. However, we currently know little about effects of such additives in the soil environment. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Alterations in pore space may also lead to their habitat loss. Likewise, as microplastic fibres may potentially release harmful contaminants into the soil in the form of additives (Kim et al., 2020) or organic pollutants associated with fibre manufacturing (Hermabessiere et al., 2017), specific microorganisms could have been affected by these new environmental conditions (Rillig, de Souza Machado, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in pore space may also lead to their habitat loss. Likewise, as microplastic fibres may potentially release harmful contaminants into the soil in the form of additives (Kim et al., 2020) or organic pollutants associated with fibre manufacturing (Hermabessiere et al., 2017), specific microorganisms could have been affected by these new environmental conditions (Rillig, de Souza Machado, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Microplastic effects on ecosystem functions and multifunctionality can be related with their shape (Lozano, Lehnert, et al., 2021; Rillig, Ryo, Lehmann, et al., 2019) and very likely with the leaching of additives to the soil matrix. Indeed, recent research showed that microplastic fibres of polyacrylicnitrile may cause toxicity in the soil inducing negative effects on soil biota due to their extractable additives (Kim et al., 2020). Polyester fibres contain different water soluble hazardous additives (Table S1), which can potentially be released into the soil, affecting soil biota communities and therefore ecosystem functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these additives may potentially leach into the soil with harmful consequences and toxic effects on soil biota. Negative effects of microplastic have been detected on nematode reproduction (Kim et al, 2020), earthworm performance (Huerta Lwanga et al, 2016), as well as on soil microorganisms. In fact, microplastics may cause a decline in soil bacterial diversity and richness (Huang et al, 2019; Fei et al, 2020), and also potentially cause negative effects on soil fungal communities (Kettner et al, 2017; Leifheit et al, 2021; Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We exposed the plastic mulch to weathering in the field before application and left it in the soil for one year before planting the lettuce, whereas Qi et al (2018) and Meng et al (2020) used pristine materials. The aging of the plastic will lead to the leakage of some plastic components (Kim et al 2020), the formation of biofilms (Amaral-Zettler et al 2020) and the change in some polymers (Chamas et al 2020). We can hypothesize that the aging of the plastics can lead to effects at smaller concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2020a) estimated a 3% drop in crop yield for every additional 100 kg ha −1 of film residue in soil. On a smaller scale, plastic debris is proven to affect soil physicochemical properties (de Souza Machado et al 2019;Qi et al 2020a) and the soil microbiome (Kim et al 2020;Qi et al 2020b) as well as enter the root system (Giorgetti et al 2020). Plastic debris also interacts with other contaminants in soil such as heavy metals (Fen Wang et al 2018) and pesticide residues (Beriot et al 2021).…”
Section: 1 Introductionmentioning
confidence: 99%